Navigating the online missiology classroom: Class design and resources for teaching missiology online - Danielson, Robert A. (Missiology, 2015)
There is a growing need for missiologists to consider the unique ways in which the discipline affects the online teaching of missions. This area of education is rapidly growing and presents challenges that need to be addressed. Especially important is the need to consider the local context of students and the types of assignments developed to encourage learning in the field. An awareness of available resources and an understanding of the changing models of learning is also a vital foundation to developing productive and effective high-quality online educational experiences.